Choice made by the nursing team, of peripheral veins for intravenous therapy in newborns - Cardoso, Juliana Maria Rêgo Maciel (2011)
The implementation of intravenous therapy in the newborn is complex and challenging. The objective of this research was to identify the peripheral veins of choice for venipuncture in newborn, and describe the criteria used by the nursing staff in the choice of these vessels. The setting was a newborn intensive care unit in Rio de Janeiro, Brazil. We interviewed ten nursing professionals from May to June 2007. The thematic analysis led to the categories: “Choose from a peripheral vein in infants: Priorities of the nursing staff” and “Criteria used and difficulties faced in choosing the veins for peripheral venipuncture. The veins of the dorsal arch of the hand were the first choice for newborn in newborn and scalp vein last choice. The selection criteria were: visualization, facility, durability and drug infused. The main difficulties in the implementation of the intravenous therapy in infants were the wear of the venous network and pain arising from multiple punctures.